الأدوات المالية و إشكالية تطبيق القيمة العادلة على ضوء النظام المحاسبي المالي و المعايير الدولية للمحاسبة Ias/ifrs - تسعديدت, بوسبعين (جامعة الوادي- University of Eloued, 2017)
financial instruments are the most trading in the global markets, this put many problematic relate measured and disclosed it in order to achieve reliability. the fair value is considered as a basis for assessing the financial instruments set by the Council of the International Accounting Standards issued by a number of international standards for accounting and financial reporting. Algeria, It’s financial accounting system evaluation method of financial instruments are obtained from the international standard setter , and this has raised other important forms of respect to the ability of the Algerian economic to achieve accounting for financial instruments in accordance with the fair value
Financial instruments and the problem of applying fair value in the light of SCF and IAS / IFRS
مقال
Keywords: financial instruments, fair value, classification, measurement, disclosure